The Quranic-based healing through sound and its psychological effect: a review of literature - Hechehouche, Oualid; Dzulkifli, Mariam Adawiah; Alias, Intan Aidura (IIUM Press, 2020)
The effects of sound in human psychology and physiology are complex. The psychology of sound, also called auditory psychology, has its own features of pitch, intensity and timbre. The study of the effect of healing through the sound of recitation the Qur’an is an important issue that has not been given sufficient attention to research. Also, Muslim believes that the Qur'an is not like other books whose sources may be obscure. Furthermore, in several verses, the Qur'an has been said as a "cure", and also it is known as a heart healer (And We send down of the Quran that which is healing and mercy for the believers, but it does not increase the wrongdoers except in loss, (Al-Israa 82). Many studies have been conducted on the effect of healing through the Qur'an in many areas. Based on the studies, the sound of recitation the Qur’an can improve the psychological and the physiological parameters including reducing heart rate, anxiety and stress, increasing mental health and memory performance for children and adults. Therefore, listening and reading the Qur’an can be recommended as supportive care improvement especially the psychological performance of people. This article reviews studies that have been conducted on Quranic recitation and the psychological effects associated with it.